Measurement of Circulating 1,25-Dihydroxyvitamin D: Comparison of an Automated Method with a Liquid Chromatography Tandem Mass Spectrometry Method - Armin Zittermann; Jana B. Ernst; Tobias Becker; Jens Dreier; Cornelius Knabbe; Jan F. Gummert; Joachim Kuhn (International Journal of Analytical Chemistry)
Background. The clinical relevance of circulating 1,25-dihydroxyvitamin D (1,25(OH)2D) is probably underappreciated, but variations in the measurement of this difficult analyte between different methods limit comparison of results. Methods. In 129 clinical samples, we compared a new automated assay with a commercially available liquid chromatography tandem mass spectrometry (LC-MS/MS) kit. Results. Median (interquartile range) 1,25(OH)2D concentrations with the automated assay and the LC-MS/MS method were 26.6 pg/mL (18.5–39.0 pg/mL) and 23.6 pg/mL (16.1–31.3 pg/mL), respectively (P=0.001). Using the method-specific cut-offs for deficient 1,25(OH)2D levels (<20 pg/mL for the automated assay and <17 pg/mL for the LC-MS/MS method), the percentage of patients classified as 1,25(OH)2D deficient was 28.7% and 27.1%, respectively. However, concordance between the two methods for deficient levels was only 62% and the concordance correlation coefficient was poor (0.534). The regression equation resulted in an intercept of −1.99 (95% CI: −7.33–1.31) and a slope of 1.27 (95% CI: 1.04–1.52) for the automated assay. The mean bias with respect to the mean of the two methods was −3.8 (1.96 SD: −28.3–20.8) pg/mL for the LC-MS/MS method minus the automated assay. Conclusions. The two methods show only modest correlation and further standardization is required to improve reliability and comparability of 1,25(OH)2D test procedures.